Efeito do laser de baixa intensidade na atividade biológica de células-tronco da polpa de dentes decíduos humanos - Antunes, Fernanda Ginani (2017)
The low-level laser therapy (LLLT) has been shown positive results in the in vitro proliferation of several cell types. The first part of the study evaluated the effect of LLLT on the proliferation and viability of stem cells from human exfoliated deciduous teeth (SHED).Cells were irradiated or not (control) with an InGaAlP diode laser (660 nm, 30 mW, continuous action mode) using two different doses (0.5 J/cm2 for 16 seconds and 1.0 J/cm2 for 33 seconds) and the three groups were analyzed at the intervals of 0, 24, 48 and 72 h.It was observed that the dose of 1.0 J/cm2 promoted an increase in cell proliferation at the 48 and 72 h intervals when compared to the control group and the dose of 0.5 J/cm2, and that cell viability was not affected by irradiation throughout the experiment. Taken together, the data showed that the LLLT parameters (660 nm, 30 mW, 1.0 J/cm2) promoted proliferation of SHEDs and maintained their viability. Based on these favorable results, the second part of the study evaluated the effect of LLLT with the same parameters on the proliferation of SHEDs cultured on PLA nanofibrous scaffolds obtained by electrospinning. This procedure allows obtaining three-dimensional scaffolds that mimic the extracellular matrix from a biomaterial with favorable physical properties and low cost.Three experimental groups (G1 - non-irradiated; G2 - irradiated with 0.5 J/cm2; G3 - irradiated with 1.0 J/cm2) were analyzed at 24, 48 and 72 h. The results indicated that PLA is not cytotoxic to SHEDs and that the groups submitted to laser therapy had higher cell growth when compared to the nonirradiated control group. Based on these findings, it was shown that PLA nanofibers are favorable scaffolds for the cultivation of SHEDs and that laser therapy stimulated the proliferation when applied to the cells cultured on this scaffold. Based on the general data obtained, it is concluded that the laser therapy in the evaluated parameters has biostimulatory effects on the proliferation of SHEDs on both the standard surface (plastic of the culture plate) and on nanostructured PLA scaffolds.